Stock markets as “simulacra”: Observation that participates - Hertz, Ellen (My University, 2000)
This article argues that popular and scientific conceptions of financial markets are structured by a moral ontology that opposes a real to a false economy. This opposition recapitulates the opposition between real and false representation, as articulated by Plato. Investment plays the ideal-typical role of the real copy, as the investor demonstrates her willingness to orient her representations of future profits around the original, the real economy of needs and goods. Speculation plays the role of the false copy or simulacrum, self-referentially mimicking the form of the real economy though circumventing its essence. While the distinction between investment and speculation breaks down in practice, it is maintained in discourse through the materialist ideologies of production and consumption. In order to jettison this discourse entirely, it is necessary to examine what is properly social in the real economy, what is properly material in the speculative economy, and how these two logics interrelate. In this enterprise, B. Latour's notion of the quasi-object as applied to financial instruments gives us a conceptual tool with which to unhinge the phantasmagoric logic of the simulacrum that underwrites representation in arid of the stock market.